Mitochondrial DNA control region haplotypes and haplogroup diversity in a sample from Brasília, Federal District, Brazil - Freitas, Jorge M.; Fassio, Levy H.; Braganholi, Danilo F. [UNESP]; Chemale, Gustavo (Elsevier, 2019)
Brazilians form one of the most heterogeneous populations in the world, as the result of five centuries of miscegenation between its native populations with migrants from Europe, Africa and Asia. The present study intended to characterize the frequencies of mtDNA haplotypes in a dataset of 306 individuals from Brasília, Federal District of Brazil. Brasília was built from scratch in the late 1950s and its construction attracted migrants from different regions of Brazil, mostly from Central-West, Northeast and Southeast regions. Due to its formation, its population is admixed. The goal of this study was to collect mtDNA population data and contribute to databases for a better use of mtDNA for forensic purposes. The haplotypes are available at EMPOP website under accession number EMP00695.
Keywords: Brazil; Central-West region; Forensic science; mtDNA control region